Analisis Perbedaan Kelengkapan Formulir Catatan Perkembangan Pasien Terintegrasi (CPPT) Berbasis Elektronik Dengan Berbasis Kertas Pada Diagnosis Skizofrenia Paranoid Di RSJD Surakarta - Ardani Setiowati; Sri Sugiarsi (Akademi Perekam dan Informasi Kesehatan Imelda, 2022)
Based on a preliminary survey at RSJD Surakarta, the completeness of filling out the electronic-based and paper-based Integrated Patient Development Record (CPPT) form with a total of 10 samples taken at random has 40% completeness on the electronic-based and 60% paper-based CPPT form. This type of research is comparative. The population in this study were all medical record documents of inpatients with a diagnosis of paranoid schizophrenia at the Surakarta Hospital in the first quarter of 2019 totaling 59 electronic patient medical record documents and 63 paper patient medical record documents in the first quarter of 2020. The sample size was obtained by the sample formula. a minimum of unpaired numerical comparative research and with a simple random sampling technique, the results obtained were 31 electronic medical record documents and 31 paper medical record documents. The results of the research on electronic-based CPPT forms on identification reviews are 100%, 100% authentication reviews, and 88% important report reviews. Meanwhile, in the paper-based CPPT form, the identification review is 97%, the authentication review is 90.5% and the important report review is 100%. In this study, the Mann-Whitney test was used as an alternative to the independent t-test which did not meet the requirements. Mann Whitney test results p-value <0.05 so ha is accepted which means there is a difference in the completeness of the electronic-based and paper-based CPPT forms. Keywords: Electronic and paper CPPT forms, identification review, authentication review, important report review